2006
DOI: 10.1179/174329306x102093
|View full text |Cite
|
Sign up to set email alerts
|

Steady state thermomechanical modelling of friction stir welding

Abstract: International audienceThis paper presents a computational method for the simulation of a welding process called friction stir welding. This simulation is divided into two main steps. The first one uses an Eulerian description of the thermomechanical problem; a 3D mixed finite element model based on a computational fluid dynamics package is used to establish the material flow, the temperature and the pressure fields during the process. These results are compared with experimental data. The second step of the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 16 publications
0
66
0
1
Order By: Relevance
“…As claimed by researchers [98][99][100], the Eulerian formulation was seldom used for thermal analysis of the process, because unlike the Lagrangian method, in the Eulerian formulation the mesh is fixed and the material can move between the boundaries. Therefore, the Eulerian setting was widely used in those processes in which the material travels through the grid such as fluid mechanics problems.…”
Section: Lagrangian Eulerian Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As claimed by researchers [98][99][100], the Eulerian formulation was seldom used for thermal analysis of the process, because unlike the Lagrangian method, in the Eulerian formulation the mesh is fixed and the material can move between the boundaries. Therefore, the Eulerian setting was widely used in those processes in which the material travels through the grid such as fluid mechanics problems.…”
Section: Lagrangian Eulerian Methodsmentioning
confidence: 99%
“…A steady state model was investigated by Bastier et al [100]. There were two different stages in the simulation.…”
Section: Lagrangian Eulerian Methodsmentioning
confidence: 99%
“…The observed difference has been related to the heat generated, due to a combination of frictional heating and plastic deformation heating, during the FSW process. Using a computational model for FSW of 7075 Al alloy, Bastier et al [25] reported that the overall magnitude of the heat generated due to plastic deformation accounts only for 4.4% of the total heat generation whereas frictional heat generation provides 95.6%. Therefore, the low or high tool rotational speeds influence the frictional conditions and hence the heat distribution in the joint, resulting in different sizes for the SZ and the HAZ.…”
Section: Effect Of Wear On Microstructuresmentioning
confidence: 99%
“…In the literature, one can find both very simple and more sophisticated modellings involving microstructural changes, all of them based on a viscoplastic formalism, whether or not using a plastic threshold. For example, the model of [Myhr and Grong 1991a;1991b] is used in [Bastier et al 2006;Feulvarch et al 2005a;2005b;Feulvarch 2006]; it takes into account the dissolution of precipitates due to the temperature evolution in aluminium alloys.…”
Section: Modelling the Processmentioning
confidence: 99%